EVIL SPIRITS IN THE DEMONOLOGICAL SYSTEM OF THE NORTH CAUCASUS - Sagaeva, Zarina; Bekoev, Vladimir; Tolasova, Irina (Revista Inclusiones, 2020)
Issues of regional culture and cultural unity of the peoples of the North Caucasus have been the object of study of many Russian scientists. At the same time, the religious beliefs of each people have unique features, as they evolved under the influence of individual cultural and historical conditions. This article reflects the specific features of the demonology of the peoples of the North Caucasus in the cultural aspect. The author conducted a comparative analysis of the mythological characters of various ethnic cultures of the region, traced their transformation under the influence of religious beliefs, and considered modern modifications of religious and mythical images. The author comes to the conclusion about the correspondence between the demonological images of various ethnic groups, the influence of mythology and religious culture, the modern transformation of images and the objective conditions of their transition to folklore. Practical use of this publication is possible in studying folklore, the regional culture of the North Caucasus, mythology, and religious studies